Revisiting the Ventral Medial Nucleus of the Hypothalamus: The Roles of SF-1 Neurons in Energy Homeostasis - Choi, Yun-Hee; Fujikawa, Teppei; Lee, JiWon; Reuter, Anne; Kim, Ki Woo (Frontiers in Neuroscience, 2013)
Obesity, diabetes, and other metabolic complications are growing concerns for public health and could lead to detrimental life-threating conditions. Neurons whose activities are required for energy and glucose homeostasis are found in a number of hypothalamic nuclei. In the early 20th century, the ventral medial nucleus of the hypothalamus (VMH) was the first site reported to play a prominent role in the regulation of energy homeostasis through control of food intake and energy expenditure. Recent studies using sophisticated genetic tools have further highlighted the importance of the VMH and have extended our understanding of the physiological role of the nucleus in regulation of energy homeostasis. These genetic studies were preceded by the identification of steroidogenic factor-1 (SF-1) as a marker of the VMH. This review focuses on the emerging homeostatic roles of the SF-1 neurons in the VMH discovered through the use of genetic models, particularly highlighting the control of energy and glucose homeostasis.